Physical and Chemical Characteristics of Durian Seed Flour (Durio zibethinus Murr) with Sodium Metabisulfite Soaking - Mustofa, Muhammad Zasir; Asmoro, Novian Wely; Handayani, Catur Budi (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2024)
Durian fruit produces waste in the form of skin and seeds that are often not utilized. Durian seeds contain carbohydrates, fats, proteins, and various other nutrients, making them suitable for use as flour in various food products. Treatment of durian seeds with thermal methods affects the browning of durian seed flour. The use of sodium metabisulfite plays a role in improving the quality of flour by deactivating enzymes that cause color changes and inhibiting microbial growth. This study used a Completely Randomized Design (CRD) with variations in sodium metabisulfite soaking time (Control, 2 hours, 2.5 hours, 3 hours, 3.5 hours) Repetition 2 times and data collection in duplicate. The stages of the study include, preparation of durian seeds, soaking, drying, grinding, and analysis of physical and chemical characteristics. The chemical characteristics of the research results showed that the water content of durian seed flour ranged from 9.53% - 13.95%. The physical characteristics of the research results showed that the Whiteness Index (WI) value ranged from 68.60 - 82.97%, there was a significant increase in WI with increasing soaking time. Water Binding Capacity (WC) ranged from 152.1 - 228.8 g/g. Oil Binding Capacity (IH) ranged from 86.17 - 109.7 g/g. Bulk density ranged from 0.77 - 0.59 g/ml. Soaking durian seeds in sodium metabisulfite solution significantly affected the physical and chemical characteristics of the resulting flour. Soaking for a longer time increased the whiteness index, water binding capacity, oil binding capacity, and decreased the bulk density of durian seed flour. Keywords: Durian seeds, sodium metabisulfite, soaking, flour.